STRATEGI PENGEMBANGAN USAHA (UKM) UNTUK MENINGKATKAN CITRA KOTA MALANG DI WISATA KULINER DAN TEMPAT PARIWISATA - Shabina Deanova; Tyna Yunita; Hendrick Moses; Rendy Ramadan (Cross-border, 2023)
Small and Medium Enterprises (SME) based on culinary enterprises is the most dominating business sector in Malang City. This research used the descriptive qualitative method and the data resources obtained from interview. This aims of this research was to describe and analyze resistance and support factors that affecting the development strategy of SME based on culinary enterprises, development strategy of SME based on culinary enterprises and tourist’s perception of the products that produced by SME based on culinary enterprises in Malang City. The result of the research showed that, first the resistance factors that affecting the development strategy of SME based on culinary enterprises are fund, materials, equipment, human resources and area. While the support factors that affecting this research are licensing, training, marketing and organization. Second development strategy of SME based on culinary enterprises are training, protection of business, development of partnerships and development of the promotions. Third tourist’s perception of the products that produced by SME are influenced by the packaging of products displayed and product innovation that created by SME enterprisebased culinary in Malang.